Using the logarithmic identity log a (b/c) = log a (b) - log a (c):
log4 (4 7/17) - log4 (3 21/68) + log4 (48)
= log4 [(4×17+7)/17] - log4 [(3×68+21)/68] + log4 (48)
= log4 (75/17) - log4 (213/68) + log4 (48)
Now, we can simplify the logarithms further by using the fact that log a (bc) = log a (b) + log a (c) and log a (b^c) = c log a (b):
= log4 (75) - log4 (17) - [log4 (213) - log4 (68)] + log4 (16×3)
= log4 (75) - log4 (17) - log4 (213) + log4 (68) + log4 (16) + log4 (3)
= log4 [(75×68×16)/(17×213×3)]
≈ log4 (4.23)
≈ 1.20 (rounded to two decimal places)
Therefore, log4 (4 7/17) - log4 (3 21/68) + log4 (48) ≈ 1.20.
Log4 (4 7/17) - log4 (3 21/68) + log4 (48)
3 answers
Log4 (4 7/17) - log4 (3 21/68) + log4 (48)=3
This is not a true statement. From the solution above, we have:
log4 (4 7/17) - log4 (3 21/68) + log4 (48) ≈ 1.20
This means that the value of the expression is approximately equal to 1.20, not 3. There is no way to manipulate the logarithms to make the expression equal to 3.
log4 (4 7/17) - log4 (3 21/68) + log4 (48) ≈ 1.20
This means that the value of the expression is approximately equal to 1.20, not 3. There is no way to manipulate the logarithms to make the expression equal to 3.